Model for the Evaluation of the EDUCOM-DIGITAL Project Effectiveness at the Santa Elena Peninsula State University Based on Plithogenic OffSet - Paola Elizabeth Cortez Clavijo; Mishelle Adriana Flores Friend; Lilibeth Alexandra Orrala Soriano; Cynthia Nataly Espíndola Vásquez; Sandra Betzabeth Maldonado López; Karla Estefanía Suarez Mena; César Teodoro Arízaga Sellan; Gerzon Alfredo Cochea Panchana (Neutrosophic Sets and Systems)
EDUCOM-DIGITAL is an educational project of the Santa Elena Peninsula State University (SEPSU) aimed at overcoming challenges related to digital educational communication at this university in this Ecuadorian province. Technological, economic, and cognitive barriers, among others, hinder the adequate development of digital educational communication in our province. From a theoretical perspective, the project contributes to generating new knowledge by developing an innovative model for integrating podcasts into teaching and scientific outreach. The uniqueness of this proposal lies in its application in vulnerable educational contexts, which will allow for the exploration of pedagogical strategies tailored to the needs of teachers and students with limited resources. Addressing this issue expands the conceptual framework of digital educational communication and provides empirical evidence of its impact on university education. In practical terms, the project will allow for the validation of existing theories on the effectiveness of digital formats in autonomous learning and scientific communication. Several studies have indicated that podcasts can improve content comprehension, facilitate access to academic information, and encourage critical reflection in students. However, their implementation at the SEPSU will allow these postulates to be tested in a real-life context, evaluating how the use of audio resources influences the acquisition of knowledge and the development of communication skills in the university community. This paper aims to propose an evaluative model for the effectiveness of this project, but this implies overcoming two challenges, which are: (1) The presence of several variables of different origins that are based on subjective perceptions and therefore present uncertainty and indeterminacy; (2) The need for a measurement scale that is sufficiently expressive of the different possible evaluations to be carried out. Therefore, we propose to base this model on the Plithogenic OffSets, which is a MultiVariate and Multidimensional theory such that the evaluations of the propositions are based on intervals with values less than 0 or greater than 1. Therefore, situations of loss or over-fulfillment can be modeled.